Pelatihan Alih Media Karya Tulis Ilmiah Menjadi Buku Digital untuk Meningkatkan Kemampuan Profesionalisme Guru - Syafruddin, Syafruddin; Ananda, Refisa; Rachmaningsih, Dewi Maharani (Jurnal Pengabdian UNDIKMA, 2023)
This community service program aims to improve the skills of teachers in transferring scientific writing media into digital books by utilizing the issues digital publishing platform. Implementing this service used training and technical assistance for teachers at Madrasah Ibtidayah (MI) Manggarupi, Madrasah Tsanawiyah (MTs) Manggarupi, and SMA PGRI Sungguminasa starting from creating an ISSUU account to publishing works. The instrument for evaluating this activity used the Context, Input, Process, and Product (CIPP) model. The training questionnaire was given via Google Form and analyzed descriptively. The result of this service activity was an increase in the ability of teachers to publish their scientific writings through digital publishing platforms. Teachers experienced the benefits of using a digital edition publishing platform to support school learning activities. The platform could also be a forum for students in these schools to publish their writings and works.